The Influence of Communication and Work Supervision on Employee Performance - Harianto, Harianto; Khair, Oki Ikbal (Indonesian Development of Economics and Administration Journal, 2025)
This research aims to determine the influence of communication and work supervision on employee performance, both partially and simultaneously, at PT. Inti Nomika Indonesia in Tangerang City. Methodology/approach – This research uses a quantitative method with a descriptive approach. The sample collection technique employs saturated sampling, and the sample obtained in this research consists of 96 respondents. Findings – It was found that. Communication has a positive and significant effect on employee performance, work supervision has a positive and significant effect on employee performance, and communication and work supervision together have a positive and significant effect on employee performance. Novelty/value – Improving skills through various training programs. Enhancing reporting systems to make them more systematic. Benchmarking is also necessary to broaden the insights of the employees of PT. Inti Nomika Indonesia in Tangerang City.